Improving Spatial Representation of Soil Moisture Through the Incorporation of Single-Channel Algorithm with Different Downscaling Approaches - Sharma J.; Prasad R.; Srivastava P.K.; Yadav S.A.; Yadav V.P. (My University, 2025)
The use of microwave observations in the low-frequency range is a complementary tool for mapping surface soil moisture. The L-band (1-2 GHz) region is a lower frequency band of microwave radiations, and currently, only two satellite soil moisture data products are available in the L-band frequency range through the satellites Soil Moisture Active Passive (SMAP) and Soil Moisture Ocean Salinity (SMOS). Both these have almost the same spatial resolution around 36-40 km. Although SMAP also provides an enhanced soil moisture product at 9 km, still finer scale information of soil moisture is required. The present study tries to enhance coarse-scale soil moisture by incorporating the single-channel algorithm (SCA). The results obtained by SCA were used as the inputs for the downscaling algorithms instead of directly using the satellite soil moisture product. Through this study, we implement and compare three approaches: approximation of thermal inertia (ATI), triangle, and dispatch methods. The results illustrated that the downscaling algorithms perform better with the estimated SMAP soil moisture through SCA in comparison to direct SMAP soil moisture, and the thermal inertia-based approach is the best performing among the three methods. © 1980-2012 IEEE.